Formas De Integração E ‘Tríade Mercantil’: O Carácter Não Ontológico Do Mercado Na Análise Institucional De Karl Polanyi (Forms of Integration and ‘Catallactic Triad’: The Non-ontological Character of Market in the Institutional Analysis of Karl Polanyi) - Machado, Nuno Miguel Cardoso (Social Science Research Network, 2013)
A análise da economia enquanto processo instituído, proposta por Polanyi, concretiza-se no estudo dos padrões institucionais que esta pode assumir empiricamente: reciprocidade, redistribuição e troca mercantil. Esta última – corporizada num sistema de mercados autorregulados – apenas se assume como forma de integração dominante nas sociedades capitalistas modernas. O estudo das formas de integração – assim como a sua extensão lógica à análise dos conceitos de comércio, dinheiro e mercado – permitirá que as ciências sociais evitem uma visão marcada pela ‘mentalidade de mercado’, ou ‘falácia economicista’. Se o comércio e o dinheiro têm acompanhado a humanidade desde os seus primórdios, os mercados são um desenvolvimento institucional bem mais recente.The analysis of the economy as instituted process, suggested by Polanyi, consists in the study of the institutional patterns which the economy may assume empirically: reciprocity, redistribution and market exchange. The last one – embodied in a system of price-making markets – only comes to be a dominant form of integration in modern capitalist societies. The study of the forms of integration – as well as its logical extension to the analysis of the concepts of trade, money and market – will allow social sciences to avoid a framework characterized by a ‘market mentality’, or ‘economistic fallacy’. Trade and money have existed since the early stages of mankind but markets are a more recent institutional development. in Teoria & Sociedade, Forthcoming
Keywords: exchange; market; reciprocity; redistribution

Karl Polanyi E O ‘Grande Debate’ Entre Substantivistas E Formalistas Na Antropologia Econômica (Karl Polanyi and the 'Great Debate' Between the Substantivists and Formalists in Economic Anthropology) - Machado, Nuno Miguel Cardoso (Social Science Research Network, 2012)
Na raiz do pensamento Polanyiano, encontra-se a distinção entre economia no sentido substantivo e economia no sentido formal. Com efeito, a concepção substantivista que define a economia como um processo instituído de interação entre o homem e o ambiente natural e social que o rodeia e resulta em contínua oferta de meios para satisfazer as necessidades humanas constitui a base do método preconizado pelo autor: a análise institucional. Com tal distinção, Polanyi (1977a) pretende evitar a "falácia economicista" que consiste na identificação automática da economia com sua forma de mercado. Ao contrário, só na moderna economia capitalista é que um "sistema de mercados formadores de preços" desempenha papel fundamental. Essas questões foram alvo de um "Grande Debate" entre as correntes substantivista – encabeçada por Polanyi – e formalista no contexto da disciplina da Antropologia Econômica.At the root of Polanyian thought, a distintiction can be found between the substantive and formal concepts of the economy. In fact, the substantivist conception, that defines the economy as an instituted process of interaction between man and its natural and social environment, which results in a continuous supply of material means to meet human needs, constitutes the basis of the method recomended by the author: institutional analysis. With this distinction, Polanyi intends to avoid the "economistic fallacy", which consists of the automatic identification of the economy in its market form. Only in the modern capitalist economy does a system of "price-making markets" play a fundamental role. These questions were amply discussed in the so-called "Great Debate" between the substantivist and formalist schools of thought in the discipline of Economic Anthropology. in Economia e Sociedade, Vol. 21, No. 1 (44), pp. 165-195
Keywords: economy; formalism; institutional analysis; market; substantivism